Unraveling the impact of a germline heterozygous POLD1 frameshift variant in serrated polyposis syndrome - Bonjoch, Laia; Soares de Lima, Yasmin; Díaz-Gay, Marcos; Dotti, Isabella; Muñoz, Jenifer; Moreira, Leticia; Carballal, Sabela; Ocaña, Teresa; Cuatrecasas, Miriam; Ortiz, Oswaldo; Castells, Antoni; Pellisé, Maria; et al. (Frontiers in Molecular Biosciences, 2023)
Serrated polyposis syndrome (SPS) is one of the most frequent polyposis syndromes characterized by an increased risk for developing colorectal cancer (CRC). Although SPS etiology has been mainly associated with environmental factors, germline predisposition to SPS could also be relevant for cases with familial aggregation or a family history of SPS/CRC. After whole-exome sequencing of 39 SPS patients from 16 families, we identified a heterozygous germline frameshift variant in the POLD1 gene (c.1941delG, p.(Lys648fs*46)) in a patient with SPS and CRC. Tumor presented an ultra-hypermutated phenotype and microsatellite instability. The POLD1 germline variant segregated in three additional SPS-affected family members. We attempted to create yeast and cellular models for this variant but were no viable. Alternatively, we generated patient-derived organoids (PDOs) from healthy rectal tissue of the index case, as well as from a control donor. Then, we challenged PDOs with a DNA-damaging agent to induce replication stress. No significant differences were observed in the DNA damage response between control and POLD1-Lys648fs PDOs, nor specific mutational signatures were observed. Our results do not support the pathogenicity of the analyzed POLD1 frameshift variant. One possible explanation is that haplosufficiency of the wild-type allele may be compensating for the absence of expression of the frameshift allele. Overall, future work is required to elucidate if functional consequences could be derived from POLD1 alterations different from missense variants in their proofreading domain. To our knowledge, our study presents the first organoid model for germline POLD1 variants and establishes the basis for its use as a model for disease in SPS, CRC and other malignancies.